2022
DOI: 10.1186/s12943-022-01518-8
|View full text |Cite
|
Sign up to set email alerts
|

Current applications and future perspective of CRISPR/Cas9 gene editing in cancer

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) system provides adaptive immunity against plasmids and phages in prokaryotes. This system inspires the development of a powerful genome engineering tool, the CRISPR/CRISPR-associated nuclease 9 (CRISPR/Cas9) genome editing system. Due to its high efficiency and precision, the CRISPR/Cas9 technique has been employed to explore the functions of cancer-related genes, establish tumor-bearing animal models and probe drug targets, vastly increasing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(110 citation statements)
references
References 217 publications
2
108
0
Order By: Relevance
“…CRISPR/Cas9 is a common gene-editing tool that uses RNA-guided nucleases to cleave foreign genetic elements. 300 307 CRISPR/Cas9 may serve as a potential method to target unique eccDNA breakpoint sequences, although it still lacks experimental evidence. 300 , 301 , 308 , 309 The effects of CRISPR/Cas9 on the elimination of eccDNA need to be further explored.…”
Section: Limitations Of Eccdnamentioning
confidence: 99%
“…CRISPR/Cas9 is a common gene-editing tool that uses RNA-guided nucleases to cleave foreign genetic elements. 300 307 CRISPR/Cas9 may serve as a potential method to target unique eccDNA breakpoint sequences, although it still lacks experimental evidence. 300 , 301 , 308 , 309 The effects of CRISPR/Cas9 on the elimination of eccDNA need to be further explored.…”
Section: Limitations Of Eccdnamentioning
confidence: 99%
“…The entire genome sequencing of mice cells showed that there were a high number of mutations after editing by CRISPR/Cas9 [121]. The off-target effect of CRISPR/Cas9 has been demonstrated in functional studies of plant genome [109,122] and clinical applications [123][124][125], indicating the CRISPR/Cas9 system's off-target effect to be a widespread phenomenon. There are two main kinds of mismatches between sgRNA and the target DNA.…”
Section: Off-target Effectmentioning
confidence: 99%
“…Although CRISPR-Cas9 delivery by using MSNs is in an initial stage and challenges still remain, the versatility of this type of nanomaterial allows multiple combinations for gene editing by carrying plasmids, sgRNA, and Cas9 mRNA, or directly the Cas9 protein. Moreover, targeting ligands can be easily incorporated into MSNs to achieve targeted CRISPR-Cas9 delivery to thus reduce the off-target effects that derive from gene editing in non-targeted tissues [ 64 ]. Importantly as a dual platform, multiple combinations for gene editing and drug therapy can be envisioned by using MSNs by preparing advanced nanodevices to solve possible biomedical needs in complex diseases or restoring sensitivity in drug-resistant diseases like cancer or infections [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeting ligands can be easily incorporated into MSNs to achieve targeted CRISPR-Cas9 delivery to thus reduce the off-target effects that derive from gene editing in non-targeted tissues [ 64 ]. Importantly as a dual platform, multiple combinations for gene editing and drug therapy can be envisioned by using MSNs by preparing advanced nanodevices to solve possible biomedical needs in complex diseases or restoring sensitivity in drug-resistant diseases like cancer or infections [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%